1990
DOI: 10.2134/agronj1990.00021962008200010011x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Management Strategies for a Short Growing Season Environment: Water‐Nitrogen Considerations

Abstract: The Southern High Plains of Texas represents the largest contiguous cotton (Gossypium hirsutum L.) production area in the USA. Water supply represents the greatest limitation to production under rainfed conditions. Where supplemental irrigation is used, growing season length represents a major limitation to attainment of high yields of desirable quality fiber and seed. The primary objective of this research project was to determine the inter‐relationships between H2O, N, and heat unit supplies as they affect l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 4 publications
3
43
0
Order By: Relevance
“…Foundation Seed, College Station, TX) was planted using a high-clearance hoe opener grain drill at ~50 kg·ha −1 sowing rate to achieve 200 plants·m Pullman soil [18]; therefore, no fertilizer N was needed to achieve the expected dryland yields for wheat [19] and cotton lint [20]. We applied no P or K fertilizer because the Pullman clay mineralogy supplies sufficient K to meet crop demand [21] and dryland crop response to broadcast applied P fertilizer has been limited for 0.76 m rows.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foundation Seed, College Station, TX) was planted using a high-clearance hoe opener grain drill at ~50 kg·ha −1 sowing rate to achieve 200 plants·m Pullman soil [18]; therefore, no fertilizer N was needed to achieve the expected dryland yields for wheat [19] and cotton lint [20]. We applied no P or K fertilizer because the Pullman clay mineralogy supplies sufficient K to meet crop demand [21] and dryland crop response to broadcast applied P fertilizer has been limited for 0.76 m rows.…”
Section: Field Experimentsmentioning
confidence: 99%
“…No fertilizer N was applied because, as previously noted, annual atmospheric deposition and mineralization for a Pullman soil totaling ~47 kg N ha −1 [18] is sufficient to achieve ~500 kg·ha −1 lint yields [20] that might be expected for dryland cotton at Bushland. The effects of other nutrients on cotton growth are not simulated by GOSSYM and were not specified [31].…”
Section: Model Uncertainty and Crop Simulationsmentioning
confidence: 99%
“…Sabbe and Zelinski (1990) point out that it is very important to understand nutrient uptake patterns for specific crops prior to interpreting the data related to plant-tissue Cotton Response to Irrigation and Nitrogen 2283 analysis, because there are differences among species, varieties, and locations. Furthermore, Morrow and Krieg (1990) reported that cotton response to N fertilization is very often difficult to predict and mostly linked to initial soil nitrate (NO 3 2 )-N level. Therefore, the availability of N from previous cultivation and residues will considerably affect the N management of the succeeding cotton crop and should be seriously considered.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of fertilizers are the major constraints in cotton production in most of cotton producing area (Morrow & Krieg, 1990). Proper fertilization practices in cotton crop ensure improved economics of production, efficiency of nutrient use, and environmental protection.…”
Section: Introductionmentioning
confidence: 99%